2005
DOI: 10.1063/1.1894985
|View full text |Cite
|
Sign up to set email alerts
|

Second order superintegrable systems in conformally flat spaces. II. The classical two-dimensional Stäckel transform

Abstract: This paper is one of a series that lays the groundwork for a structure and classification theory of second order superintegrable systems, both classical and quantum, in conformally flat spaces. Here we study the Stäckel transform ͑or coupling constant metamorphosis͒ as an invertible mapping between classical superintegrable systems on different spaces. Through the use of this tool we derive and classify for the first time all two-dimensional ͑2D͒ superintegrable systems. The underlying spaces are exactly those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
176
0
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(181 citation statements)
references
References 16 publications
1
176
0
4
Order By: Relevance
“…(In [26,25] the details of the proofs are given and the results are extended to systems with degenerate potentials.) We have shown that all these systems are Stäckel equivalent to superintegrable systems on spaces of constant curvature, the potentials of which have already been classified in detail [36,30,29].…”
Section: Conclusion and Further Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(In [26,25] the details of the proofs are given and the results are extended to systems with degenerate potentials.) We have shown that all these systems are Stäckel equivalent to superintegrable systems on spaces of constant curvature, the potentials of which have already been classified in detail [36,30,29].…”
Section: Conclusion and Further Resultsmentioning
confidence: 99%
“…If λ is the metric of a space that admits a nondegenerate superintegrable system, then it is always possible to choose coordinates x, y such that λ 12 = 0 [41]. In [25] we prove the following basic result. where either…”
Section: The Stäckel Transform For Two-dimensional Systemsmentioning
confidence: 99%
“…This suggests that to classify all such superintegrable systems we can restrict attention to these two constant curvature spaces, and then obtain all other cases via Stäckel transforms. We are making considerable progress on the classification theory [21], though the problem is complicated.…”
Section: Discussionmentioning
confidence: 99%
“…Two dimensional second order superintegrable systems have been studied and classified by the author and his collaborators in a recent series of papers [18,19,20,21]. Here we concentrate on three dimensional (3D) systems where new complications arise.…”
Section: Introduction and Examplesmentioning
confidence: 99%
See 1 more Smart Citation